Osteoblastic metastasis from signet ring cell gastric cancer in a young male - Ermiş, Fatih; Erkan, Melih E; Besir, Fahri H; Oktay, Murat; Kutlucan, Ali; Aydın, Yusuf (Turkish Journal of Gastroenterology, 2014)
Abstract Bone metastasis is common in patients with lung, prostate, and breast cancers but it isn’t common in stomach cancer. Gastric carcinoma infrequently metastasizes to the bone and rarely in an osteoblastic form. Herein we presented a rare case of signet ring cell gastric adenocarcinoma in early stage with osteoblastic metastasis. To our knowledge our case was the youngest signet cell gastric cancer patient with osteoblastic bone metastasis reported in literature.